A NEW APPROACH TO THE PREVENTION OF INTRA-OPERATIVE COMPLICATIONS IN THE CORRECTION OF COMPOUND MYOPIC ASTIGMATISM USING THE RELEXS®MILE METHOD - O. A. Klokova; V. V. Myasnikova; S. N. Sakhnov; R. O. Damashauskas (Офтальмохирургия, 2017)
Purpose. To study the efficiency of a preoperative inhalation session of oxygen-xenon mixture in the mode of analgosedation for stressunstable patients at the preoperative preparation stage for the ReLEx®SMILE method.Material and methods. The study group consisted of 11 patients (mean age 22.76±1.43 years) with a high degree of anxiety (>46 points), according to the Spielberger State-Trait Anxiety Inventory (STAI). The laser correction by the ReLex® SMILE technology was planned for them (average spherical equivalent (SE) 3.38±0.39D) using the VisuMax™ 500 kHz device (Carl Zeiss Meditec AG). As a preoperative preparation, they underwent the inhalation of an oxygen-xenon mixture in the analgosedation mode. The sessions were performed using the anesthesia XENA-01 device, operating on a closed loop, thereby the xenon exposure was carried out in sub-narcotic concentrations – 35-40% (up to 1/3 МАC).Results. During the analgosedation session with the oxygen-xenon mixture before the ReLEx® SMILE, the hemodynamic and ventilation parameters in the patients of the study group remained stable. By the 20th minute the patients calmed down, fell asleep, heart rate decreased up to 55.4±5.3 per minute. The 40% xenon exposition was 20 minutes. The xenon consumption was 4.5±0.7 liters per session.During the ReLex® SMILE, the patients, remaining fully conscious, behaved adequately and calmly. The stage of interface applanation to the cornea, its centering, femto-dissection occurred without complications in all patients. The planned refractive result was achieved in 100% of cases (the mean SE was 0.25±0.1D). The next day after the procedure, the UCVA in all patients was 0.9-1.0.Conclusion. The analgosedation session with an oxygen-xenon mixture provides an adequate nociceptive and anti-stress protection, guarantees safe laser ophthalmic interventions in emotionally labile patients. The obtained results of the study allow to consider this premedication method before the femto-laser correction of ReLEx® SMILE as a new approach to the prevention of such an intraoperative complication as the vacuum loss.